2016
DOI: 10.1161/strokeaha.116.013326
|View full text |Cite
|
Sign up to set email alerts
|

Degree and Timing of Intensive Blood Pressure Lowering on Hematoma Growth in Intracerebral Hemorrhage

Abstract: Background and Purpose— Degree and timing of blood pressure (BP) lowering treatment in relation to hematoma growth were investigated in the Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial-2 (INTERACT2). Methods— INTERACT2 was an international clinical trial of intensive (target systolic BP [SBP], <140 mm Hg) versus guideline-recommended (SBP, <180 mm Hg) BP lowering in 2839 patients within 6 hours of spontaneous intracerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 11 publications
1
37
0
1
Order By: Relevance
“… 2 Although no significant effects on haematoma growth were detected in INTERACT-2, 2 secondary analysis suggested that blood pressure lowering did attenuate bleeding in a dose-dependent manner. 23 The interaction between baseline systolic blood pressure and treatment in our study suggests that participants with lower blood pressure were more likely to benefit from tranexamic acid. This finding could have been confounded by stroke severity, given that larger haematomas have increased blood pressure and worse outcomes.…”
Section: Discussionmentioning
confidence: 60%
“… 2 Although no significant effects on haematoma growth were detected in INTERACT-2, 2 secondary analysis suggested that blood pressure lowering did attenuate bleeding in a dose-dependent manner. 23 The interaction between baseline systolic blood pressure and treatment in our study suggests that participants with lower blood pressure were more likely to benefit from tranexamic acid. This finding could have been confounded by stroke severity, given that larger haematomas have increased blood pressure and worse outcomes.…”
Section: Discussionmentioning
confidence: 60%
“…A post-hoc analysis of INTERACT2 did find that greater reduction in SBP was associated with reduced hematoma growth (13.3 mL for less than 10 mm Hg, 5.0 mL for 10–20 mm Hg, and 3.0 mL for at least 20 mm Hg, P <0.001). In addition, the lowest mean hematoma growth was in patients in the intensive treatment arm who achieved a target SBP at less than 1 hour compared with those patients who achieved target SBP at later time points 37 .…”
Section: Summary Of Data and Recent Guidelinesmentioning
confidence: 89%
“…BP should not be excluded as a contributing factor to IVH growth. Whilst baseline BP per se does not appear to be a major factor in the pathogenesis of IVH, there was a trend towards a greater IVH volume growth at higher average achieved systolic BP over the first 24 h. Indeed, further analyses of the INTERACT2 study showed that rapid and sustained systolic BP reduction was associated with less ICH hematoma growth over 24 h [ 6 ]. Another consideration relates to whether intensive BP reduction is associated with a lower risk of developing IVH.…”
Section: Discussionmentioning
confidence: 99%